Acute promyelocyte leukemia arose from CALR 1 mutated post essential thrombocythemia- myelofibrosis with splanchnic vein thrombosis: A case report. (2021) - Morsia, E; Goteri, G; Torre, E; Garvey, KB; Discepoli, G; Tassoni, A; Mancini, S; Giantomassi, F; Poloni, A; Olivieri, A; Rupoli, S
Abstract: Major disease complications for patients with essential thrombocythemia (ET) include thrombosis and fibrotic or leukemic transformation. Calreticulin (CALR) mutation type 1 frequencies in ET are estimated between 7% and 11% and ET patients carrying CALR type 1 mutation are associated with lower risk of thrombosis but higher risk of myelofibrosis transformation compared to ET patients with JAK2 mutation. Leukemic transformation rates at 20 years are estimated at less than 5% for ET and risk factors for leukemic transformation are advanced age, thrombosis history, leukocytosis, and anemia. Amongst the subtypes of blast phase myeloproliferative neoplasms, acute promyelocytic leukemia is extremely rare. Herein, we present a case of a promyelocytic blast crisis of post-ET myelofibrosis with associated life-threatening splanchnic vein thrombosis. This case suggests that inflammation plays a key role in thrombotic events and fibrotic/leukemic transformation in ET patients, regardless the molecular landscape.